IMPORTANCE OF HABITAT USE OF MACROBENTHIC MOLLUSCS IN THE INTERTIDAL ZONES OF INDIAN SUNDARBAN - SAU, SUSOVAN; NAGESH , T. S.; TRIVEDI , R. K.; DUBEY, S. K.; BHAKTA, DIBAKAR; JANA, SUSMITA; BODA , S. (Journal of the Inland Fisheries Society of India, 2026)
In the present study importance value and habitat use of macrobenthic molluscs pertaining to rapid diversity inventory in the estuarine zones of Sundarban, West Bengal, India was studied for a period of six months in three zones (western, central and eastern) and 21 sampling stations. A total 12 species of molluscs belonging to eight families were recorded. The species composition consisted of Littoraria melanostoma, Littoraria scabra, Austropilula beddomeana, Cerithidea obtusa, Pirenella cingulata, Telescopium telescopium, Pythia plicata, Cassidula nucleus, Nerita balteata, Platevindex tigrinus, Tegillarca granosa and Psammacoma sp. Molluscan species were distributed in mud flat (42%), trunks and roots of mangrove forest trees (50%) and in both (8%). P. cingulata recorded consistently the highest relative abundance, relative density and importance value index in all the zones as well as in the overall study area of Indian Sundarban. The overall highest relative frequency, however, was recorded for T. telescopium in all the zones. The overall importance value ranged between 75.81 (P. cingulata) and 4.92 (P. tigrinus). This study suggested that mangrove regions in the Indian Sundarban should be monitored in order to maintain this ecologically sensitive ecosystem in a sustainable manner.